Islam, Ethnicity and Secession: Forms of Cultural Mobilization in Aceh Rebellions - Ali Munhanif (Studia Islamika, 2016)
This article explains the appeal of two different remarkable forms of cultural mobilization within the Aceh secessionist movement. The first form is the emergence of the Darul Islam (DI) rebellion in the 1950s; and the second is the rise of the Free Aceh Movement (Gerakan Aceh Merdeka, GAM) during the 1980s and 1990s. Recent trends in Aceh’s political dynamics pose a striking puzzle as to how the institutional arrangements created by the government of Aceh have complicated the political dimensions of GAM. Some institutions have shaped new patterns of Aceh-Jakarta relations, but others represent a revitalization of the previous Aceh-Islamic state rebellion under DI/TII. What are the likely causes for the re-emergence of Islam coming to the center stage of Aceh politics? This article argues that the primary forces that have driven these variations in the two periods of rebellion were the interaction between the institutional design of the nation-state and the considerable opportunity for cultural mobilization at a particular institutional juncture. Secessionist ideologies such as those in Aceh are shaped and mediated by the institutional context in which they manifest.DOI: 10.15408/sdi.v23i1.2659